Tumor transition zone: A putative new morphological and functional hallmark of tumor aggressiveness - Bustuoabad, Oscar David (2005)
A small primary or secondary tumor load can occasionally induce more deleterious effects than a histologically identical larger one. In the four murine models studied herein this enhanced tumor aggressiveness could not be attributed to NRAS mutations or other hereditary changes, differential vascularization of live tumor tissues, or necrosis content. Instead, the main tumor feature associated with a more aggressive behavior was the presence of a high number of vessels, sometimes filled with inflammatory cells, inside a tumor area, which we have identified and designated as the transition zone between the live and the necrotic zones. Our experiments suggest that during tumor growth, different cachectic factors are produced within the transition and necrotic zones by dying tumor cells and by tumor infiltrating macrophages only reaching the general circulation through the vessels present in the transition zone. Therefore, a small tumor displaying high vascularization of its transition area could be harmful to its host, while, in contrast, a large tumor could behave as a relatively benign one if its transition zone exhibited little or no vascularization, and in consequence its cachectic factors remained “trapped.” Similar histological images to those observed in mice were seen in a significant percentage of human cancer biopsies, raising the possibility that such images might have a prognostic value.